THE RELATIONSHIP OF PRAYER MOVEMENT WITH LOW BACK PAIN: LITERATURE REVIEW - Fahira Jannataynidan; Tanisya Dwi Maulida (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2024)
Low Back Pain (LBP) or commonly referred to Nyeri Punggung Bawah is a musculoskeletal disorder that is usually caused by poor body activity. LBP can also be caused by various musculoskeletal diseases, psychological disorders and improper mobilization. Another cause is physical factors, namely improper position while sitting, sleeping or standing for a long time can also cause LBP complaints. This research aims to study the relationship between prayer practices and muscle flexibility to understand its potential impact on LBP. The design used in this study is a literature review. In this study, we used databases such as Google Scholar with the keywords Low Back Pain, prayer movements, and literature review, Prayer movements consisting of certain postures such as standing, bowing, prostrating, and sitting, can contribute to muscle flexibility through balanced muscle performance. Proper execution of prayer postures, especially the act of bowing, can help maintan spinal alignment, improve blood circulation, and prevent spinal disorders, which can potentially affect LBP. Suggestions for this study can use a more varied database to get more literature from around the world. In addition, future studies can use research designs such as systematic review, cross-sectional, or other studies that can see the relationship between prayer movements and LBP.